Effects of the optical isomers of pentazocine and cyclazocine upon responding maintained by second-order schedules of intravenous morphine reinforcement in squirrel monkeys (Saimiri sciureus). - Henry, Margaret E. (University of Ottawa (Canada), 1978)
Effects of the optical isomers of pentazocine and cyclazocine upon responding maintained by second-order schedules of intravenous morphine reinforcement in squirrel monkeys (Saimiri sciureus). Monkeys were trained under schedules in which either every 10th (FR 10) or 30th (FR 30) response during a fixed-interval of 50 min (FI 50 min) produced a brief presentation of an external signal (S), unaccompanied by an injection;. the first ratio-requirement completed after expiry of the FI produced the signal (S) accompanied by an i.v. infusion of morphine. Morphine pretreatment (1-5.6 mg/kg i.m.) suppressed drug-seeking behaviour in a dose-dependent manner. Naloxone pretreatment (0.1 mg/kg) when given alone exerted no effect on response-rate; when given in combination with graded doses of morphine, morphine-induced suppression of drug-seeking behaviour was antagonized. 1-Pentazocine (0.1-10 mg/kg i.m.) pretreatment suppressed responding more effectively than d-pentazocine at equivalent doses. 1-Cyclazocine (0.01-1.0 mg/kg i.m.) suppressed responding whereas d-cyclazocine at equivalent doses did not. Pentazocine isomers failed to antagonize the effects of morphine pretreatment. 1-Cyclazocine antagonized the effects of morphine pretreatment more effectively than pentazocine but d-cyclazocine was ineffective at equivalent doses. Cyclazocine and pentazocine differ in their capacity: (i) to suppress morphine-reinforced responding, and (ii) to antagonize the effects of morphine pretreatment upon such patterns of drugseeking behaviour. The stereoisomers of these drugs were found to be less potent than naloxone in reversing morphine-induced suppression of morphine-seeking behaviour.
Keywords: Psychology, Experimental.